AFLP and AMP Fingerprints as Markers to Evaluate Genetic Differences between Medicago truncatula Line Jemalong and 2HA, a New Line Produced by in vitro Culture Selection - R. R. Irwanto; R. J. Rose (Institute for Research and Community Services (LPPM) ITB, 2008)
A new line, Medicago truncatula cv. Jemalong 2HA (herein known as 2HA) has been developed via repetitive regeneration and selection of M. truncatula cv. Jemalong. During somatic embryogenesis, 2HA produces 500 times more embryos than its progenitor, Jemalong. It is interesting to study if those two lines are isogenic or has genetic differences. The main objectives of the study was to evaluate the genotypic differences between Jemalong and 2HA also to evaluate the methylation event in 2HA utilized two DNA fingerprinting techniques, i.e AFLP fingerprints (Amplified Length of Polymorphism) and AMP (Amplified Methylation Polymorphism). The results showed that AFLP analysis using eight primers combinations could not detect any differences between Jemalong and 2HA. However, using AMP methylation sensitive primers it could detect 15 polymorphisms out of 840 markers. These results lead to a conclusion that Jemalong and 2HA are isogenic lines. 2HA may have higher regeneration capacities due to methylation process which occurs during the production of 2HA through repetitive regeneration cycles.